PERILAKU BERBAHASA DI PONDOK PESANTREN ADLANIYAH KABUPATEN PASAMAN BARAT - M. Ihsan (Universitas Andalas, 2011)
This article shows the langauge behaviors in Pondok Pesantren Adlaniyah Pasaman Barat. The research look into student activities in the class and out of class. The results show that switching and mixing code appear because some factors: mother language, age, motivations, habit, teachers, and environment.